Пьезоэлектрические преобразователи энергии волнения моря - Scubilin, M. D. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The possibility of converting ocean wave energy into electrical energy is analyzed; to this end, it is proposed to convert the vibrations of a floating structure’s components into discrete force inputs on piezoelectric transducers, then store the electrical energy they generate via rectifiers, and subsequently use it to power autonomous, maintenance-free, sea-based information sources.